Pengaruh Kualitas Produk terhadap Perkembangan Usaha Kuliner di Rumah Makan Incor Laru Kecamatan Tambangan - Muhammad Sangkot Pangidoan Nst; Muhlisah Lubis; Muhammad Ardiansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study was conducted by Muhammad Sangkot Pangidoan (Student ID: 20090033) under the title “The Effect of Product Quality on Business Development in the Culinary Sector at Rumah Makan Incor Laru, Tambangan District, Mandailing Natal Regency.” This quantitative research employed multiple linear regression analysis. Data were collected through questionnaires distributed to 96 respondents using a simple random sampling technique. The objective of this study was to determine and examine the effect of product quality on the business development of Rumah Makan Incor Laru. The research was carried out in Tambangan Tonga Village from December 2023 to August 2025. The independent variable in this study is product quality, while the dependent variable is business development. The results show that product quality has a positive and significant effect on business development, with a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 0.522, indicating that 52.2% of changes in business development are explained by product quality, while the remaining 47.8% are influenced by other factors outside this study. The simple regression equation obtained is Y = 24.583 + 0.275X, with a t-count of 9.340 greater than the t-table value of 2.372, meaning the hypothesis is accepted.